Rare earth metal doped transition metal electrocatalyst and preparation method and application thereof
By using the transition metal electrocatalyst Eu-CoS1.097, a rare earth metal-doped transition metal electrocatalyst in zinc-air batteries, the problem of slow kinetics of oxygen reduction reaction and oxygen precipitation reaction in zinc-air batteries is solved, and efficient and stable catalytic effects are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411788232.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
AI Technical Summary
In the oxygen reduction reaction and oxygen precipitation reaction of existing zinc-air batteries, the kinetics of the adsorption and desorption process of oxygen-containing intermediates is slow, which restricts the energy conversion efficiency. Most commercial catalysts are precious metal-based catalysts, which have problems of scarce resources and high costs.
A rare earth metal-doped transition metal electrocatalyst Eu-CoS1.097 was developed. By doping Eu in Co, the electronic state of the catalyst is optimized, and a catalyst with a hollow spherical structure is prepared by combining materials such as PVP and NH2-H2BDC, using hydrothermal reaction and etching of thioacetamide.
This catalyst significantly improves the catalytic activity and stability of the oxygen-induced oxygen reaction, reduces production costs, and has a wide range of application prospects in the cathode of rechargeable zinc-air batteries.
Smart Images

Figure CN119786631A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a MOF derivative catalyst, and in particular to a rare earth metal-doped transition metal electrocatalyst and a preparation method and application thereof. Background Art
[0002] In the social context of energy shortage and environmental pollution, researchers have focused on the field of new energy storage and conversion technology and have made great progress. Among them, zinc-air batteries have received special attention due to their high energy density, low cost, and environmental friendliness. The rechargeable zinc-air battery system generates and stores electrical energy through redox reactions between the positive and negative electrodes. Its charging and discharging processes correspond to the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) occurring on the air cathode, respectively. However, the adsorption and desorption kinetics of oxygen-containing intermediates in the ORR and OER reactions are slow, which restricts the energy conversion efficiency of zinc-air batteries. Therefore, the air cathode of the battery requires a suitable catalyst to accelerate the reaction. Currently, most commercial catalysts are precious metal-based catalysts such as Pt, Ru, and Ir, which have the shortcomings of scarce resources and high prices, increasing the production cost of zinc-air batteries. Based on this, the development of efficient and inexpensive oxygen electrocatalysts is a top priority for promoting the full commercialization of rechargeable zinc-air batteries. Summary of the invention
[0003] Purpose of the invention: The first purpose of the present invention is to provide a rare earth metal-doped transition metal electrocatalyst having excellent electrocatalytic activity for oxygen evolution reaction; the second purpose of the present invention is to provide a method for preparing the rare earth metal-doped transition metal electrocatalyst; the third purpose of the present invention is to provide an application of the rare earth metal-doped transition metal electrocatalyst.
[0004] Technical solution: The rare earth metal-doped transition metal electrocatalyst of the present invention has a chemical formula of Eu-CoS 1.097 , which is a crystalline and amorphous structure, in which the Eu element exists in the form of a single atom.
[0005] Preferably, the molar ratio of Eu to Co is 1:3-5.
[0006] Preferably, the catalyst is a hollow spherical structure.
[0007] The method for preparing the rare earth metal-doped transition metal electrocatalyst of the present invention is characterized by comprising the following steps:
[0008] (1) dissolving polyvinylpyrrolidone (PVP) and NH2-H2BDC in a solvent to obtain a mixed solution;
[0009] (2) adding cobalt salt and europium salt to the mixed solution, mixing evenly, and performing a hydrothermal reaction to obtain a EuCo-MOF precursor;
[0010] (3) Adding EuCo-MOF precursor and thioacetamide (TAA) into the solvent for hydrothermal reaction, TAA releases S 2- A rare earth metal-doped transition metal electrocatalyst with a hollow spherical structure is obtained by etching.
[0011] NH2-H2BDC is an organic ligand whose functional group anchors Co 2+ The metal organic framework structure is formed. Europium salt is used as a dopant to introduce Eu elements, and then the unfilled f orbital electrons of rare earth elements are combined with CoS 1.097 The d orbital coupling of TAA optimizes the electronic state of the transition metal and improves its catalytic activity. PVP is a morphology-directing agent, which makes the EuCo-MOF precursor obtain a relatively uniform spherical structure. 2- The etching effect finally gives Eu-CoS 1.097 Hollow spherical structure.
[0012] Preferably, in step (1), the solvent is a mixed solution of C2H5OH and DMF; further preferably, the volume ratio of C2H5OH to DMF is 1:1.
[0013] Preferably, in step (2), the temperature of the hydrothermal reaction is 120 to 180° C., and the reaction time is 12 to 24 hours.
[0014] Preferably, in step (2), the cobalt salt is CoCl2, CoSO4 or Co(NO3)2; the europium salt is Eu(NO3)3 or EuCl3.
[0015] Preferably, in step (3), the temperature of the hydrothermal reaction is 100 to 180° C., and the reaction time is 1 to 5 hours.
[0016] Preferably, in step (3), the mass ratio of the EuCo-MOF precursor to thioacetamide is 1:(1-5).
[0017] Preferably, in step (3), the solvent is ethanol.
[0018] The rare earth metal-doped transition metal electrocatalyst of the present invention is used as an oxygen evolution catalyst.
[0019] Invention Mechanism: The present invention uses cobalt salt as cobalt source, NH2-H2BDC as ligand, PVP as morphology directing agent, and rare earth europium salt as dopant to synthesize EuCo-MOF precursor. Due to the low solubility of NH2-H2BDC in water, NH2-H2BDC is dissolved in a mixed solution of C2H5OH / DMF according to the principle of like dissolves like, and a spherical precursor is hydrothermally synthesized with the assistance of PVP. Then, the S released by TAA hydrolysis is 2- The etching process obtains a hollow spherical structure, and finally a crystalline / amorphous Eu-CoS1.097 catalyst doped with a single atom of rare earth Eu is obtained.
[0020] The Eu-doped crystalline / amorphous oxygen electrocatalyst prepared by the present invention has uniform size, controllable morphology, and a typical hollow spherical structure, which not only makes the catalyst have good structural stability, but also provides a larger specific surface area with its spherical surface and cavity structure, exposing more active sites. The rare earth element Eu has a unique f orbital electron, which can be successfully coupled with the d orbital of the transition metal Co, optimizing the overall electronic state of the catalyst and improving the OER performance.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The catalyst effectively improves the activity of the catalyst by doping Eu into Co; (2) The catalyst has a typical hollow spherical structure with uniform size and regular shape. Its spherical surface and cavity structure effectively increase the active sites and show high catalytic activity and stability for OER; (3) The preparation method is simple and efficient; (4) The catalyst can be well applied to the cathode of rechargeable zinc-air batteries and has broad application prospects in the future energy storage industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a SEM image of the catalyst prepared in Example 2;
[0023] Figure 2 HRTEM image of the catalyst prepared in Example 2;
[0024] Figure 3 is a STEM image of the catalyst prepared in Example 2;
[0025] Figure 4 An enlarged STEM image of the catalyst prepared in Example 2;
[0026] Figure 5 The XRD pattern of the catalyst prepared in Example 2;
[0027] Figure 6 OER polarization curves of the catalysts prepared in Example 2, Example 6 and Example 7;
[0028] Figure 7 OER polarization curves of the catalyst prepared in Example 2, commercial RuO2, and the catalyst synthesized in Comparative Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with embodiments.
[0030] Example 1
[0031] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0032] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol CoCl2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0033] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0034] Example 2
[0035] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0036] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0037] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0038] Example 3
[0039] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0040] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol CoSO4 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0041] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0042] Example 4
[0043] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0044] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol EuCl3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0045] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0046] Example 5
[0047] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0048] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full sonication, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu2(CO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0049] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0050] Example 6
[0051] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0052] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.6 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0053] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0054] Example 7
[0055] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0056] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 1.0 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0057] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0058] Example 8
[0059] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0060] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 120 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0061] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0062] Example 9
[0063] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0064] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 180 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0065] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0066] Example 10
[0067] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0068] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 12 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0069] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0070] Embodiment 11
[0071] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0072] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 24 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0073] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 200 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0074] Example 12
[0075] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0076] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0077] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 100 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0078] Embodiment 13
[0079] The rare earth metal-doped transition metal electrocatalyst of the present invention comprises the following steps:
[0080] (1) 500 mg PVP and 150 mg NH2-H2BDC were dissolved in 40 mL C2H5OH and DMF mixed solution (volume ratio 1:1), and after full ultrasonic dissolution, 0.8 mmol Co(NO3)2 and 0.2 mmol Eu(NO3)3 were added, stirred for 30 min, and then transferred to a 50 ml polytetrafluoroethylene liner, and hydrothermally reacted at 150 ° C for 20 h. After cooling, the mixture was washed with ethanol three times and dried for use;
[0081] (2) Weigh 100 mg of the precursor obtained in step (1) and dissolve it together with 500 mg of TAA in 30 ml of C2H5OH. After stirring for 5 min, transfer it to a 50 ml polytetrafluoroethylene liner and perform hydrothermal reaction at 160° C. for 2 h. After cooling, wash with ethanol to obtain the final product.
[0082] Comparative Example 1
[0083] On the basis of Example 2, Eu(NO3)3 was not added and other conditions remained unchanged.
[0084] Structural characterization
[0085] (1) The catalyst prepared in Example 2 was physically characterized by TEM, HAADF-STEM, and XRD.
[0086] By SEM( Figure 1 )、HRTEM( Figure 2 ) can show that the prepared catalyst has a typical hollow nanosphere morphology with uniform size.
[0087] From the STEM dark field image ( Figure 3 ) it can be seen that Eu exists in the form of a single atom, as shown in the circle in the figure.
[0088] From the enlarged STEM image ( Figure 4 ) it can be seen that the crystalline-amorphous regions of the catalyst can be observed, and obvious grain boundaries can be observed, and the bright Eu atoms are mostly distributed in the amorphous regions.
[0089] From the XRD pattern ( Figure 5 ) can be obtained, and the numerous diffraction peaks of the catalyst are consistent with the standard card (CoS 1.097 The results of the STEM dark field image are consistent with those of the previous study, and no diffraction peak of Eu element was observed, which proves that Eu element exists in the form of single atom.
[0090] Performance Testing
[0091] Oxygen evolution reaction (OER) activity test, test method: 5 mg catalyst, 900 μL deionized water and 100 μL naion solution (5wt%) were mixed and ultrasonically mixed to prepare catalyst ink. Then 10 μL catalyst suspension was dropped on the surface of glassy carbon electrode and dried at 40 °C. The OER polarization curve of the sample was tested by three-electrode system using CHI 760D electrochemical workstation, in which the solution was 1.0 M KOH solution and the scan rate was 5 mV s -1 .
[0092] 1. The OER activity of the catalysts doped with different Eu contents in Example 2, Example 6 and Example 7 was tested. The test results are as follows: Figure 6 shown.
[0093] Depend on Figure 6 It can be seen that the catalysts prepared in Example 2, Example 6 and Example 7 have a current density of 10 mA cm -2 The overpotentials at 316mV, 321mV, and 338mV are respectively. With the increase of Eu doping amount, the activity of the catalyst increases first and then decreases, indicating that the appropriate Eu content is crucial to the OER performance of the catalyst. Too much or too little rare earth content will restrict the OER activity of the catalyst. This also confirms to a certain extent that rare earth Eu exists as a co-catalyst rather than an active center.
[0094] 2. The catalyst prepared in Example 2 and commercial RuO2 were used as reference catalysts to investigate the OER activity of different catalysts in alkaline media. The test results are as follows: Figure 7 shown.
[0095] Depend on Figure 7 The polarization curve of the catalyst for OER shows that the catalyst prepared in Example 2 has a high current density of 10 mA cm -2 The overpotential at is 316 mV, which is much smaller than 342 mV of the comparative catalyst and 349 mV of commercial RuO2.
[0096] The OER activity of the catalyst prepared in Example 2 in alkaline electrolyte is much higher than that of the catalyst prepared in the comparative example and the commercially available RuO2 catalyst, which is mainly attributed to its unique hollow sphere structure and the result of electronic optimization brought about by Eu single atom doping.
Claims
1. A rare earth metal-doped transition metal electrocatalyst, characterized in that: Its chemical formula is Eu-CoS 1.097 , which is a crystalline and amorphous structure, in which the Eu element exists in the form of a single atom.
2. The rare earth metal-doped transition metal electrocatalyst according to claim 1, characterized in that: The molar ratio of Eu to Co is 1:3-5.
3. The rare earth metal-doped transition metal electrocatalyst according to claim 1, characterized in that: The catalyst is a hollow spherical structure.
4. A method for preparing the rare earth metal-doped transition metal electrocatalyst according to claim 1, characterized in that: The following steps are involved: (1) dissolving polyvinyl pyrrolidone and NH2-H2BDC in a solvent to obtain a mixed solution; (2) adding cobalt salt and europium salt to the mixed solution, mixing evenly, and performing a hydrothermal reaction to obtain a EuCo-MOF precursor; (3) Adding EuCo-MOF precursor and thioacetamide into solvent for hydrothermal reaction, TAA releases S 2- A rare earth metal-doped transition metal electrocatalyst with a hollow spherical structure is obtained by etching.
5. The method for preparing a rare earth metal-doped transition metal electrocatalyst according to claim 4, characterized in that: In step (2), the temperature of the hydrothermal reaction is 120 to 180° C., and the reaction time is 12 to 24 hours.
6. The method for preparing a rare earth metal-doped transition metal electrocatalyst according to claim 4, characterized in that: In step (3), the temperature of the hydrothermal reaction is 100 to 180° C., and the reaction time is 1 to 5 hours.
7. The method for preparing a rare earth metal-doped transition metal electrocatalyst according to claim 4, characterized in that: In step (3), the mass ratio of the EuCo-MOF precursor to thioacetamide is 1:(1-5).
8. The method for preparing a rare earth metal-doped transition metal electrocatalyst according to claim 4, characterized in that: In step (1), the solvent is a mixed solution of C2H5OH and DMF.
9. The method for preparing a rare earth metal-doped transition metal electrocatalyst according to claim 4, characterized in that: In step (3), the solvent is ethanol.
10. Use of the rare earth metal-doped transition metal electrocatalyst according to any one of claims 1 to 3 as an oxygen evolution catalyst.
Citation Information
Cited By
Preparation method for precisely constructing transition-rare earth bimetallic monatomic material based on confinement strategy of soft-hard acid-base theory and application of transition-rare earth bimetallic monatomic material in lithium-oxygen battery
CN121583931A
Preparation method of transition-rare earth double-metallic single-atom material based on soft-hard acid-base theory limited strategy and application thereof in lithium-oxygen battery
CN121583931B